A palatalização das alveolares e velares no contexto de /i/ na fala manauara - Evangelista, Camilla dos Santos (2018)
The present dissertation aims to investigate the phonetic realization of the alveolar /t/, /d/, /n/, /l/ and velars /k/ and /g/ in the context of /i/ in the Manaus’ community speak, verifying a possible palatization process of these phonemes. It is a research of a sociolinguistic approach, in the context of Gerative Phonology, which seeks to verify a natural class of sounds in the Manaus’ community speak, between the alveolar and velar, when approximated to the palatal vowel /i/, which plays a regent role in the process of palatalization, being the trigger of such process, independent of the allophones and neutralizations of the verified phonemes. It is examined whether this palatalization process occurs in any position in the word and if there is any social variant of gender, age or educational level that guides this occurrence. The theory that supports this analysis is the Phonological Traits Geometry, proposed by Clements (1985), which is represented by an arboreal system, which analyzes the internal structure of speech sounds, evidencing the way these sounds interact in the phonological systems. As a methodological procedure, we have pre-selected the Phonological Phonetic Questionnaire (PPQ), reading of phrases and texts, 118 words, divided among the studied phonemes, in which they occur in the context previous to /i/, being: 20 words with /t/ 20 words with /d/, 24 words with /l/, 16 words with /n/ in diminutive, 18 words with /l/ in diminutive, 20 words divided between /k/ and /g/. Twenty-four participants from Manaus from different parts of the city were interwied, divided between 12 females and 12 males, from 18 to 35 years old, from 36 to 55 years old and from 56 years old, with a schooling level since elementary school until with higher education, completed or not. For data collection, the procedure was done by recording individual interviews. The data were transcribed phonetically with the use of the International Phonetic Alphabet – IPA. After, they were tabulated in Excel program of Windows, in which were crossed the linguistic occurrences and social factors. In the discussion of the results, it was verified that there is a natural class occurrence in the Manaus’ community speak, between the alveolar and velar, in the context of /i/, evidencing that the process of palatalization is a process of phonological variation consolidated in the Manaus’ community speak, different from other regions of Brazil. KEY WORDS: natural sound class; alveolars; velars; palatal; context of /i/; Manaus’ community speak.